Preventive treatments for osteoradionecrosis in patients undergoing radiotherapy: scoping review - Quitral , Rodrigo (2024)
Objetives: To describe preventive treatments to avoid osteoradionecrosis (ORN). Materials and Methods: An exploratory systematic review of the available literature on preventive treatments for ORN was carried out using the PubMed, EBSCO and Scopus search engines. Studies from 2018 were included, available in English or Spanish. Results: 37 articles were obtained; 16 duplicates were discarded. When reviewing the title and abstract, 11 were included for full text reading. Once analyzed, 4 were discarded, leaving 7 included in this study. The use of antibiotic prophylaxis has discrepancies regarding its effectiveness; studies affirm that its use is essential to reduce ORN. At the same time, it is said that there is no pathophysiological justification for its prophylactic use. Hyperbaric oxygen therapy was described to prevent and treat ORN, it is suggested as an adjuvant in surgery for irradiated patients, but its use prophylactically is not supported. Platelet-rich plasma does not have favorable results to reduce the incidence of ORN and the use of tocopherols plus antibiotics is recommended to facilitate healing. Conclusions: Current literature describes various treatments to prevent ORN, however, there is no standardized protocol in dosage or time nor sufficient evidence to determine which is most effective. More studies are required to decide which preventive treatment to use to prevent ORN